2013
DOI: 10.1002/adfm.201301045
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Micelle Nanoparticles Encapsulating a Non‐Fluorescent Near‐Infrared Organic Dye as a Safe and Highly‐Effective Photothermal Agent for In Vivo Cancer Therapy

Abstract: Photothermal therapy (PTT), as a minimally invasive and highly effective cancer treatment approach, has received widespread attention in recent years. Tremendous effort has been devoted to explore various types of photothermal agents with high near-infrared (NIR) absorbance for PTT cancer treatment. Despite many exciting progresses in the area, effective yet safe photothermal agents with good biocompatibility and biodegradability are still highly desired. In this work, a new organic PTT agent based on polyethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
197
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(201 citation statements)
references
References 42 publications
1
197
0
1
Order By: Relevance
“…5,6 In recent years, photothermal therapy (PTT), a minimally invasive and highly efficient antitumor approach, has been demonstrated to enhance tumor therapeutic efficacy and reduce side effects in numerous pre-clinical animal studies. 2,[7][8][9][10] PTT functions with the assistance of certain photothermal agents, which can convert near-infrared (NIR) laser light into heat and ablate tumor tissue by inducing hyperthermia. 2,11 Therefore, it is essential to fabricate a novel bifunctional biomaterial with photothermal therapeutic capacity for treating tumor cells and bone regeneration capacity for repairing bone defects derived from surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In recent years, photothermal therapy (PTT), a minimally invasive and highly efficient antitumor approach, has been demonstrated to enhance tumor therapeutic efficacy and reduce side effects in numerous pre-clinical animal studies. 2,[7][8][9][10] PTT functions with the assistance of certain photothermal agents, which can convert near-infrared (NIR) laser light into heat and ablate tumor tissue by inducing hyperthermia. 2,11 Therefore, it is essential to fabricate a novel bifunctional biomaterial with photothermal therapeutic capacity for treating tumor cells and bone regeneration capacity for repairing bone defects derived from surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrating the potential of CPNPs as PTT agents have been carried out by Liu et al 12,13,33 Their group demonstrated that polypyrrole and PEDOT:PSS NPs can both act as effective PTT agents. 12,13 Separately, NPs composed of 2-ethylhexyl cyclopentadithiophene copolymerized with 2,1,3-benzothiadiazole or 2,1,3-benzoselenadiazole synthesized by MacNeill et al also proved to be effective PTT agents.…”
Section: Discussionmentioning
confidence: 99%
“…agents based on PEGylated micelles encapsulating a heptamethine indocyanine dye, IR825 [40]. The IR825-PEG nanoparticles showed much better photothermal stability compared to ICG, efficient tumor passive homing as a result of the enhanced permeability and retention (EPR) effect of cancerous tumors, and were able to induce effective photothermal tumor ablation under NIR laser irradiation.…”
Section: Nir Dye-containing Micellesmentioning
confidence: 99%
“…Several commonly used NIR dyes in PTT are listed in Fig. 1 [24,31,[38][39][40][41]. Generally speaking, many NIR dyes can simultaneously serve as a fluorescent imaging probe as well as a photothermal agent [24,34,36].…”
Section: Nir Dye-containing Micellesmentioning
confidence: 99%